2022
DOI: 10.3390/vaccines10071137
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak and BNT162b2 mRNA Vaccination Coverage in a Correctional Facility during Circulation of the SARS-CoV-2 Omicron BA.1 Variant in Italy

Abstract: Background. The recent spread of the highly mutated SARS-CoV-2 Omicron variant (B.1.1.529) has raised concerns about protection against COVID-19 in congregate settings such as prisons, characterized by a high risk of transmission and possible difficulties in obtaining adequate vaccination coverage. The present study aims to investigate the spread of an outbreak of COVID-19 in an Italian correctional facility during the dominant circulation of the Omicron BA.1 variant, and also considers BNT162b2 mRNA vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
5
1
Order By: Relevance
“…As reported in other studies, 16–36 the most striking reduction in comparison with the ancestral virus was found in the antibody response toward the Beta and Omicron variants, in both CO and inmates. Indeed, 91.2% and 93.9% of CO and 85.1% and 92.8% of inmates showed a ≥ 2-fold reduction in the median VN titer against the Beta and Omicron variants, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As reported in other studies, 16–36 the most striking reduction in comparison with the ancestral virus was found in the antibody response toward the Beta and Omicron variants, in both CO and inmates. Indeed, 91.2% and 93.9% of CO and 85.1% and 92.8% of inmates showed a ≥ 2-fold reduction in the median VN titer against the Beta and Omicron variants, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…In the correctional facility under study, the prevalence of inmates that have received two vaccine doses was similar to that observed in the Italian general population, whereas the percentage of those receiving the third dose was lower. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly however, the modelling indicates that high coverage immunisation alone is insufficient in preventing COVID-19 outbreaks. This concern may become increasingly evident if additional new variants emerge and vaccine-conferred cross-protection wanes [29].…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, healthcare professionals had higher workloads and professional responsibilities. The onset of this pandemic has highlighted the numerous criticalities at the organizational level involving both the national healthcare and the judicial systems [ 2 , 3 ]. Inside the prisons, inmates and staff share a confined environment that could act as a reservoir for epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare personnel faced an unknown situation, aggravated by the presence of psychosocial risk factors, such as long work shifts, emergency/urgency management without knowledge of the case, and high emotional load deriving from constant contact with high-profile situations [ 8 , 9 ]. This set of factors has caused general uncertainty, making prisons a potentially work-related stress risk context and burnout [ 3 , 10 ]. Burnout is a syndrome that causes suffering and physical, mental, psychological, and/or social dysfunctions, which occur when the demands coming from the job are not adequate to the skills, resources, or needs of the worker [ 11 ].…”
Section: Introductionmentioning
confidence: 99%